ASSESMENT OF STRUCTURAL ELEMENTS DETERIORATED IN SEMI ARID ENVIRONMENTAL CONDITIONS - KHAN, MOHAMMED FARAAZ (2022)
Deterioration of concrete is a prominent occurrence that happens due to several factors surrounding a structure making the place inhabitable with a risk to life and property. These factors and the impact of deterioration depend upon the surrounding environmental conditions of the structure and vary for different geographical locations. The deterioration of concrete in a structure if assessed properly can be stopped from propagating further and economical solutions can be proposed to rehabilitate the structure. This dissertation aims to find the most prominent type of deterioration using different testing methods in semi-arid environmental conditions like the United Arab Emirates. It further aims to assess the data retrieved by statistical analysis to find its effect on the structural elements, such as the slabs, column and beams. The statistical assessment of the data provides significant information about the deterioration and its effect on the structural elements. Furthermore, the dissertation progresses by investigating the effect of deterioration on the design forces by modelling a structure with the acquired data from the site and comparing it with a non-deteriorated structural model of the same. Analysing the design forces helps to assess the effect of deterioration on various structural elements. Moreover, the dissertation also portrays the effect of deterioration on the most effected structural element which are the columns and asses the loss in capacity due to deterioration. The assessment and the interpretation using statistical analysis and modelling of the structure along with design helps to understand the effect of deterioration on structural elements in semi-arid environmental conditions.